Mastitis, somatic cell count and its impact on dairy product quality... An omission in Colombia: a literature review - Riveros-Galán, David S.; Obando-Chaves, Mónica (Revista Colombiana de Ciencias Pecuarias, 2020)
Mastitis is the most common disease in dairy herds and the main cause of economic losses in milk production worldwide. This inflammatory reaction of the mammary gland affects the quantity, composition and quality of milk produced and its suitability for the dairy industry. Despite of its importance, Colombia has no regulations on somatic cell count (SCC); that is, no official upper limits have been established for the dairy industry. The current quality-based payment system for raw milk does not encourage local producers to reduce the level of somatic cells. Consequently, Colombia is at a disadvantage compared to countries that include this parameter in their payment schemes and subscribe to international free trade agreements, affecting the competitiveness of the Colombian dairy sector. This article reviews the types of somatic cells, the microbiology of mastitis, its etiology and diagnosis, the changes that generate the composition of milk, and the impact of high SCCs on the quality of dairy products, such as yogurt, cheese, and milk powder. The final section offers a reflection on the problem of high SCCs in Colombia and the lack of regulations in this regard.